The Hounds of Heaven - Judd, Andrew James Eric (Auckland University of Technology, 2012)
"The Hounds of Heaven" describes a girl's descent into and recovery from a psychotic episode. The version included here is not a finished version.
Keywords: Filmscript; Schizophrenia